2019
DOI: 10.1097/pcc.0000000000001870
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Exposure to Opioid and Benzodiazepine Medications for Pediatric Cardiac Intensive Care Patients: A Quality Improvement Project*

Abstract: Objectives: To evaluate the effect of implementation of a comfort algorithm on infusion rates of opioids and benzodiazepines in postneonatal postoperative pediatric cardiac surgery patients. Design: A quality improvement project, using statistical process control methodology. Setting: Twenty-five-bed tertiary care pediatric cardiac ICU in an urban academic Children’s hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…21 To this end, new sedation protocols, focused on benzodiazepine-sparing strategies, have been implemented in the PICU. 22 As a benzodiazepine-sparing strategy, this study used a delayed initiation of continuous infusion and an early association of adjuvant therapies. Recent treatment guidelines 5,6 favor the use of dexmedetomidine, leaving benzodiazepines as a second-line option.…”
Section: Discussionmentioning
confidence: 99%
“…21 To this end, new sedation protocols, focused on benzodiazepine-sparing strategies, have been implemented in the PICU. 22 As a benzodiazepine-sparing strategy, this study used a delayed initiation of continuous infusion and an early association of adjuvant therapies. Recent treatment guidelines 5,6 favor the use of dexmedetomidine, leaving benzodiazepines as a second-line option.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the impact of SA regimens on clinical outcomes in critically ill infants and children over the past decade (Table 1) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Most of these studies were single-center studies conducted in tertiary or quaternary PICUs, i.e., a mix of cardiac, medical, and surgical patients.…”
Section: Sedation and Analgesia Regimens In The Pediatric Intensive C...mentioning
confidence: 99%
“…Furthermore, although a number of studies have demonstrated safety in using dexmedetomidine as a primary sedative agent, the adoption of dexmedetomidine as a primary sedative in pediatric critical care is still lagging (6,(24)(25)(26). Of the 11 studies reviewed above, only three (27%) utilized dexmedetomidine as a first-line sedative agent (6,8,13).…”
Section: Challenges With Implementation Of Sedation and Analgesia Reg...mentioning
confidence: 99%
“…In this study, the children received morphine and midazolam according to an algorithm based on regular pain and distress assessments by the nursing staff. Donnelan et al (23) showed recently that the implementation of an algorithm reduced opioid and benzodiazepine dosing in children after cardiac surgery. More than two thirds of the subjects in our study received midazolam at some point during their intensive care admission, and only half of them needed a midazolam infusion.…”
Section: Optimal Analgosedation After Cardiac Surgerymentioning
confidence: 99%
“…In this study, the children received morphine and midazolam according to an algorithm based on regular pain and distress assessments by the nursing staff. Donnelan et al (23) showed recently that the implementation of an algorithm reduced opioid and benzodiazepine dosing in children after cardiac surgery.…”
Section: Optimal Analgosedation After Cardiac Surgerymentioning
confidence: 99%